The Influence of Filler Loading on Mechanical Properties of Rice Husk Reinforced High Density Polyethylene - Tan Yusoff, Tuan Mohd Faizie (Universiti Teknologi PETRONAS, 2010)
The aim of this project was to investigate the influence of varying filler loading on composite mechanical properties. The filler used in this research was rice husk and the matrix was high density polyethylene (HOPE). The particle size of the filler was 0.5 mm. Particulate size of' rice husks were compounded together with the matrix polymer and moulded into dog-bone shaped specimens using an injection moulding machine. In the sample preparation, rice husks were prepared using four different filler loadings which were 0, 5, 10 and 15 wt.%. The effect of the coupling agent on the mechanical properties was also investigated by incorporating 2% maleated polyethylene (MAPE) at three different filler loadings which were 5, 10 and 15 wt. %. From the microstructure observation, the surface characteristic of filler was changed when it has been dried in an oven during filler preparation process. After the drying process, the surface of rice husk appeared to be smoother than before the drying process and the ridges were less visible from the surface. Results obtained from tensile test showed that tensile strengths of the composites decreased with increasing filler loading. With the addition of compatibilizing agent, tensile strength of the composites was improved as much as 14% as filler was incorporated into the matrix at 5 wt.%. For the flexural strength, it was observed that flexural strength increases gradually with increase in filler loading. Flexural strength decreased by 16 % as 5 % filler loading added to the composite. However the flexural strength of the composites increased gradually as filler content increased to I() and 15 wt. %. Microstructural observation of the tensile fractured surfaces of samples without added compatibilizing agent showed poor compatibility of the filler-matrix as evidenced by filler debonding and pull-out. in the case of the composites with compatibilizing agent, the interfacial bonding between the filler and the matrix polymer was stronger, resulting in fracture at the filler itself and not at the interface.